Peningkatan Potensi Ikan Baji - Baji (Grammoplites scaber) Dan Proporsi Bagian Tubuh Sebagai Sumber Bahan Baku - Ayu Diana; Ahmad Fauzan Lubis (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Baji-baji fish is able to fish as a food that is a source of nutrients that are important to the process of human survival. The purpose of that is need for efforts in increasing the potential fish wedge-wedge through the study of its chemical composition analysis. The method used is the method of experiments with three (3) three-time treat and deuteronomy. Treat is a comparison of fish from different sections namely caput, truncus, cauda with a complete random design (RAL) non factorial. Observations made was the analysis of the chemical composition (proximat). Baji-baji fish contain moisture content (64%), protein (15%), lipids (6%), ash (5%), and carbohydrate (10%). The proportion of body parts on a fish advantage on any part of it that is a protein (truncus, 15.97%), lipids (truncus, 10.40%), carbohydrates (cauda, 12.55%). Baji-baji fish is a relatively cheap products but have a good nutrient content for consumption, of the increase in potential fish baji-baji has a similar nutritional content with other commercial fish nutrient content.